Free Radical Pharmacology and its role in various diseases - Gupta, Priya; Jyoti, RB; Gupta, Saibya (Journal of Drug Delivery and Therapeutics, 2019)
Free Radicals are molecules with an unpaired electron and are important intermediates in natural processes. Free radicals are very unstable and react quickly with other compounds, and try to capture the needed electron to gain stability. Once the process is started, it can cascade, and finally results in the disruption of a living cell. Generally, harmful effects of reactive oxygen species on the cell are most often like damage of DNA, oxidations of polydesaturated fatty acids in lipids, oxidations of amino acids in proteins, oxidatively inactivate specific enzymes by oxidation of co-factors. Free radicals cause many human diseases like cancer Alzheimer’s disease, cardiac reperfusion abnormalities, kidney disease, fibrosis, etc. The free radicals formed in our body are combated by antioxidants that safely interact with free radicals and terminate the chain reaction before vital molecules are damaged. Excessive exercise has been found to increase the free radical level in the body and causes intense damage to the Regular physical exercise enhances the antioxidant defense system and protects against exercise induced free radical damage.Keywords: Radicals, Free Radicals, Reactive oxygen species, Anti-oxidant, Redox signaling.